Adult Attachment Questionnaire: evidence of validity in a sample of IPVAW offenders - Osa-Subtil, Iria de la; Arias Astray, Andrés; Mateo Fernandez, Pedro Vicente; de Dios-Duarte, María José (Frontiers in Psychology, 2024)
Introduction Adult attachment can be understood as a cognitive and emotional system concerning oneself and others, based on previous attachment experiences throughout life. This system automatically affects relationships with others. Because of its importance in the interpersonal domain, it has been studied on numerous occasions in research on intimate partner violence. The aim of this study was to obtain evidence of validity of the Adult Attachment Questionnaire (AAQ) in a sample of 331 men convicted of intimate partner violence against women (IPVAW). Methods The AAQ assesses adult attachment style in four dimensions that, together, yield four attachment categories. A psychometric analysis was performed, including reliability analysis and confirmatory factor analysis of the items, which ratified the factorial structure of the questionnaire. For a correct fit of the model, it was necessary to eliminate 4 of the items from the original scale. Results A latent profile analysis was also carried out, which identified four attachment styles: secure, preoccupied/anxious, avoidant/dismissing and fearful. Reliability indices were adequate. In general, the attachment profiles obtained ranges and means similar to those found in the general population study. The distribution of attachment styles was not equal: 50.57% of the participants presented secure attachment, 4.57% avoidant/dismissing attachment, 36.9% preoccupied/anxious, and 8.57% fearful. Discussion In conclusion, a valid and reliable instrument was determined based on the original AAQ scale to measure attachment in men convicted of IPVAW.